Universities in Transition: Foregrounding Social Contexts of Knowledge in the First Year Experience - Michell, Dee (University of Adelaide Press, 2014)
Universities are social universes in their own right. They are the site of multiple, complex and diverse social relations, identities, communities, knowledges and practices. At the heart of this book are people enrolling at university for the first time and entering into the broad variety of social relations and contexts entailed in their 'coming to know' at, of and through university. By recasting 'the transition to university' as simultaneously and necessarily entailing a transition of university - indeed universities - and of their many and varied constitutive relations, structures and practices, the contributors to this book seek to reconceptualise the 'first-year experience' in terms of multiple and dynamic processes of dialogue and exchange amongst all participants. They interrogate taken-for-granted understandings of what 'the university' is, and consider what universities might yet become.